Bahasa Arab Serapan Dalam Bahasa Indonesia (Studi Kasus pada Akun Youtube The Sungkars) - Mawardi, Mawardi; Alandira, Palendika (Lughaat: Journal of Arabic Linguistics, 2025)
This study aims to identify and analyze loanwords from Arabic that have been integrated into the Indonesian language, with a case study focusing on the dakwah content from the YouTube channel The Sungkars, titled “Ustadz Ini Jawab Semua Pertanyaan Sulit Tentang Tuhan Dan Agama!!” (This Ustadz Answers All Difficult Questions About God and Religion!!). The main focus lies on the form, meaning, and semantic adaptation of Arabic terms used in religious discourse. The method employed is descriptive-analytic, with data collected through documentation and literature study. Data were analyzed using morphological and semantic approaches to reveal phonological transformations and meaning shifts. The findings show that many Arabic terms such as ilmu (knowledge), takdir (destiny), qadarallah (God’s will), akidah (creed), musyrik (polytheist), taat (obedient), salat (prayer), and konsekuensi (consequence) have been fully or partially absorbed into Indonesian, with meanings adapted to suit the context of dakwah and the Islamic cultural discourse in Indonesia. This absorption process not only enriches the Indonesian lexicon but also reflects the development of Islamic discourse in contemporary Muslim society through popular media.